Spindle-to-Cortex Communication in Cleaving Frog Eggs - Mitchison, Timothy J. (Cold Spring Harb Symp Quant Biol, 2017)
During cytokinesis, the mitotic spindle communicates with the cell cortex to position a cleavage furrow that will cut through the cell in the plane defined by the metaphase plate. We investigated the molecular basis of this communication in Xenopus laevis eggs, where the signal has to travel ~400 μm in ~30 min to reach the cortex from the first anaphase spindle. At anaphase onset, huge microtubule asters grow out from the poles of the spindle and meet at the plane previously defined by the metaphase plate. This disc-shaped boundary plane recruits the chromosome passenger complex (CPC) and centralspindlin to antiparallel microtubule bundles. It grows out to the cell cortex as the asters expand, where it induces the furrow. CPC and centralspindlin were not recruited to boundaries between asters from different spindles, suggesting a role of chromatin in triggering the CPC-positive state. Recruitment of CPC to aster boundaries was reconstituted in an extract system, and we observed that recruitment was stimulated by proximity to chromatin. Finally, we discuss models for molecular processes involved in initiation and growth of the CPC-positive disc that communicates the position of the metaphase plate to the cortex over hundreds of micrometers in frog eggs.